RT-QuIC Reactivity in the Brain and Other Organs and Tissues in Early, Middle-early, Middle-late and Terminal Stages of Scrapie Agent 263K Intracerebral Infection in Hamsters - Donglin Liang; Chumou Liu; Kang Xiao; Yuan Wang; Donghua Zhou; Xiaoxi Jia; Yuezhang Wu; Xiaoping Dong; Qi Shi (Zoonoses, 2025)
<!-- named anchor --> Objective: This study was aimed at analyzing the distribution and progression of prion seeds across the central nervous system (CNS) and peripheral tissues, by evaluating the real time quaking-induced conversion (RT-QuIC) reactivity of the brain, and other organs and tissues, from hamsters in early, middle-early, middle-late and terminal stages of intracerebral infection with scrapie agent 263K. <!-- named anchor --> Methods: Brain, skin and other organ specimens were collected at approximately 20, 40, 60 and 80 (terminal stage) days post-inoculation, and homogenates were prepared. Protein misfolding cyclic amplification (PMCA) and RT-QuIC were used for sample detection. The 50% seeding dose (SD 50) values for prion seeding were calculated with the Spearman-Karber method, and RT-QuIC reactivity lag times were compared among tissues and time points. <!-- named anchor --> Results: RT-QuIC indicated positive reactions in brain tissue samples across all time points (20–80 dpi), and increasing seeding capacity and decreasing lag times were observed during the incubation period. In peripheral tissues, including the heart, liver, spleen, lung, colon and skin, RT-QuIC positivity showed delayed onset, appearing at later stages (≥40 dpi) than observed in the brain. The brain exhibited significantly higher SD 50 values than peripheral tissues, thus reflecting greater seeding capacity. Prion seeds were widely distributed in the CNS and peripheral tissues at the terminal stage, and the highest RT-QuIC positivity and SD 50 values were observed in the brain. <!-- named anchor --> Conclusions: Prions were widely distributed in the CNS and peripheral tissues of scrapie-infected hamsters, and CNS tissues exhibited a particularly high level of reactivity and seeding capacity in the RT-QuIC assay.